Sociological and religious interpretations of Adinkra symbols: qualitative analysis of the 2025 inaugural outfit of Ghana's president - Mensah, Ronald Osei; Bordoh, Anthony; Acquah, Andrews; Bruce-Amartey Jnr, Eric; Nunoo, Papa Kofi (Frontiers in Sociology, 2025)
IntroductionAdinkra symbols, deeply embedded in Ghanaian culture, serve as potent non-verbal communicative tools that convey philosophical, religious, and sociopolitical meanings.MethodsThis study explores the sociological, religious, and fashion interpretations of the Adinkra symbols incorporated into the 2025 inaugural outfit of Ghana's President. Anchored in a qualitative research design and aligned with a constructivist research philosophical position, the study draws on insights from 28 purposively selected participants, including traditional leaders, fashion designers, museum curators, and cultural preservatists.Results and discussionThe findings reveal that “Sankofa”, “Gye Nyame”, “Nyame Dua”, and “Dwennimmen”, key symbols present in the attire, collectively signify governance introspection, divine authority, ethical leadership, and humility in power. Through the lens of Symbolic Interactionism and the Semiotic Theory of Fashion, the study demonstrates how these symbols serve as ideological markers, reinforcing national identity, political philosophy, and ethical governance. The results highlight the critical role of indigenous symbolism in shaping public perceptions of leadership, fostering national unity, and maintaining cultural continuity in Ghana's political landscape. The study calls for the integration of traditional symbols into governance, education, and leadership training to strengthen national identity and ethical governance.